LEARNING MODEL IMPROVED THINKING SKILLS TO IMPROVE THE STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING - Yus Alvar Saabighoot; Maman Rumanta (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research is motivated by the low quality of science learning in elementary schools. The objective of this research is to produce a product in the form of developing a learning model improved thinking skills to improve the student learning outcomes. This research uses a Research and Development approach. The research phase includes (a) preliminary study, (b) identification results which are used as the basis for model development, and (c) the models that have been developed are then tested extensively. During the model trial, modifications were made to the implementation of the model; adjustments were made according to the needs of teacher performance improvement. There is always an improvement in the model design, implementation, and evaluation of every trial that has been carried out. The results of the extensive trials show that the learning model improved thinking skills has a good effect on improving the student learning outcomes. Based on the statistical test through t-test = 0.05 (95% significance) obtained a significant difference in the learning outcomes in each trial. In conclusion, the learning model improved thinking skills can improve student learning outcomes in science learning and can improve the teacher’s performance in science learning. Keywords: Learning Model; Improved Thinking Skills